SCREENING ANEMIA PADA IBU HAMIL DI PUSKESMAS BERNUNG KABUPATEN PESAWARAN LAMPUNG - Yeti Septiasari; Dzul Istiqomah Hasyim; Nurwinda Saputri (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2020)
Anemia is a condition in which the number and size of red blood cells or concentrations of hemoglobin fall below the established cut-off value, consequently damaging the blood's capacity to transport oxygen throughout the body. Anemia in pregnancy is a maternal condition with hemoglobin (Hb) levels < 11 gr% in the I and III trimesters while in the second trimester hemoglobin levels < 10.5 gr%. Pregnancy anemia is called "potentional danger to mother and child", which is why anemia requires serious attention from all relevant parties in the health service. Mortality and morbidity of pregnant women, maternity and nifas are still a major problem in developing countries including Indonesia. The WHO estimates that worldwide more than 585,000 mothers die while pregnant or in labor. The purpose of this activity is to help health workers detect HB levels of pregnant women and provide information on the importance of Hb levels in the blood for pregnant women. The method for this implementation activity is carried out by providing health education on counseling about pregnancy anemia and also conducting hb examination directly in pregnant women using HB sahli or HB digitally, this activity is carried out in three stages, namely planning, implementation and evaluation, this activity shows positive things in pregnant women with increasing knowledge about anemia in pregnancy with hb test results carried out.